Biodiversity of Birds in the Green Urban Area of Petrochemical Industry, Palembang, South Sumatra, Indonesia - Yona Selvia Arma Dewita; Hilda Zulkifli; Harmida Harmida (Sriwijaya Journal of Environment, 2016)
Abstract: The study on "The Biodiversity of Birds in the Region of Green Open Space (GOS) of The Petrochemical Industry, Palembang, South Sumatra, Indonesia" was conducted from August to September 2014 with the objective to determine the diversity of bird species. The method used to inventory bird species was Indice Ponctuels' Abondance (IPA) method. The results of the study revealed that there were at least 19 species of birds included in 14 families, in which four of the bird species were the species protected by the law, namely Halcyonchloris, Haliasturindus, Halcyonsmyrnensis, and Nectariniajugularis. The plant species as the habitat of the birds included Pterocarpus indicus Willd. (16.74%), Polyalthialongifolia Sonn. (14.02%), Cocosnucifera L. (12.98%), Elaeisguineensis Jacq. (7.76%) and Mangiferaindica L. (7.71%) with the diversity index of 2.96. These data prove that the area of green urban industry can also serve as a habitat for wildlife such as birds provided that the management of the green open space remains the concern of the industry.Key words:  Birds Biodiversity, Urban Industrial AreaAbstrak (indonesian): Penelitian “Keanekaragaman Burung di Kawasan  Ruang  Terbuka  Hijau  (RTH) Industri petrokimia, Palembang, Sumatra Selatan, Indonesia” dilakukan pada bulan Agustus sampai dengan September 2014 bertujuan  untuk mengetahui keanekaragaman jenis burung,. Metode yang digunakan metode Indice Ponctuels’ Abondance (IPA) untuk inventarisasi jenis burung. Hasil penelitian mencatat terdapat minimal 19 jenis burung yang tercakup dalam 14 famili., dimana diantaranya tercatat 4 jenis burung yang merupakan jenis yang sudah dilindungi undang-undang  yaitu Halcyon chloris, Haliastur indus, Halcyons myrnensis, dan Nectarinia jugularis. Jenis tumbuhan sebagai habitat burung tercatat Pterocarpus indicus Willd. (16,74%), Polyalthialongi folia Sonn. (14,02%), Cocosnucifera L. (12,98%), Elaeisguineensis Jacq. (7,76%) dan Mangiferaindica L. (7,71%) dengan indeks keanekaragaraman (diversity index)  2,96. Data ini membuktikan bahwa pada kawasan green urban industry juga dapat berfungsi sebagai habitat satwa seperti burung dengan catatan pengelolaan ruang terbuka hijau tetap menjadi perhatian industri.Kata Kunci: keragaman burung, daerah industri perkotaan